2022
DOI: 10.1186/s12891-022-05381-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of preoperative Deep Venous Thrombosis (DVT) following elderly intertrochanteric fractures and development of a risk prediction model

Abstract: Background This study aimed to investigate the prevalence of preoperative deep venous thrombosis (DVT) following intertrochanteric fractures in the elderly and identify the associated factors, based on which a risk prediction model was developed. Method This was a retrospective single-center study of elderly patients presenting with intertrochanteric fractures between our institution between January 2017 and December 2020. Patients' duplex ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…For example, PDW was an independent predictor for postoperative DVT events of people experienced cervical carcinoma [ 57 ], and for preoperative DVT of ones followed foot who experienced fractures [ 58 ]. As the same combination of D-Dimer with PDW, or TT in our study, it was considered to have a significant ability to distinguish between DVT and non-DVT in other results [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 89%
“…For example, PDW was an independent predictor for postoperative DVT events of people experienced cervical carcinoma [ 57 ], and for preoperative DVT of ones followed foot who experienced fractures [ 58 ]. As the same combination of D-Dimer with PDW, or TT in our study, it was considered to have a significant ability to distinguish between DVT and non-DVT in other results [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 89%
“…A retrospective study by Song et al reported that a lower albumin level was the independent risk factor for preoperative DVT in 266 patients [ 25 ]. Wang et al reported that reduced albumin was associated with preoperative DVT in a risk prediction model [ 26 ]. In a meta-analysis, Wang et al found that albumin < 35 g/L was a risk factor for preoperative DVT [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nomogram showed good predictive performance after internal and external validation. Elevated D-dimer levels and hypoproteinemia are recognized risk factors for DVT in orthopedic patients, and their relevance has been widely discussed in the literature [3,9,21,40]. Albumin has heparin-like efects and its low levels induce hyperibrinogenemia and platelet aggregation, a process that can be reversed by albumin infusion [35].…”
Section: Discussionmentioning
confidence: 99%